Prehistoric human impacts on California birds: evidence from the Emeryville Shellmound Avifauna - Broughton, John (American Ornithologists' Union (AOU), 2004)
Journal Article The abundance of artiodactyls, marine mammals, waterfowl, seabirds, and other animals in 18th- and 19th-century California astonished early explorers, and the incredible wildlife densities reported in their accounts are routinely taken as analogues for the original or pristine zoological condition. However, recent analyses of archaeological fish and mammal materials from California and elsewhere in western North America document that those early historic-period faunal landcsapes represent poor analogues for prehistoric environments, because they postdate a dramatic 16th- or 17th-century population-crash of native hunters. The superabundance of tame wildlife witnessed during the early historic period may only reflect population irruptions that followed the demise of their main predators. While analyses of archaeological faunas from California have documented that prehistoric peoples had substantial impacts on populations of fish and mammals, harvest pressure on bird populations has yet to be documented. The hypothesis that prehistoric hunters caused depressions of avian taxa is tested here through a description and analysis of the Emeryville Shellmound avifauna: the first substantial, well-documented archaeological bird sequence for the late Holocene of California. A total of 64 species is represented by the 5,736 identified bird specimens derived from the stratified Emeryville deposits that date from between 2,600 and 700 years ago; waterfowl, cormorants, and shorebirds dominate the collection. Chrono-stratigraphic trends in relative taxonomic abundances and age structure within those groups are consistent with long-term anthropogenic depressions resulting from expansion of regional human populations over the occupational history of the mound. In general, large-sized bird species, those that occupied habitats closer to bayshore human residences, and those that were otherwise sensitive to human hunting pressure decreased in numbers over time. In the waterfowl assemblage, geese (Branta canadensis, B. hutchinsii, Anser albifrons, Chen caerulescens, C. rossii) declined significantly over time as compared with ducks, and the remains of the largest-sized geese (B. canadensis moffitti, A. albifrons, C. caerulescens) declined as compared with the smaller ones (e.g. B. hutchinsii, C. rossii). As hunting returns from local patches decreased over time, ever-increasing use was made of more distant, marine-oriented duck taxa - namely scoters (Melanitta fusca and M. perspicillata). Double-crested Cormorants (Phalacrocorax auritis) were especially hard-hit by human harvesting activities, which caused the extirpation of local island-based colonies; changes in the relative age and species composition of the regional Phalacrocorax fauna; and, ultimately, a nearly complete abandonment of cormorant hunting. Finally, the largest species of shorebirds-Marbled God wits (Limosa fedoa), Long-billed Curlews (Numenius americanus), and Whimbrels (N. phaeopus) - declined significantly over time, in comparison with smaller shorebird species. None of those patterns are correlated with changes in pertinent paleoenvironmental records that might indicate that they were caused by climate-based environmental change. They suggest, however, that activities of human foragers had a fundamental influence on the late Holocene avian fauna of the region, and that records of bird abundances, distributions, and behavior from the early historic period are anomalous in the context of the past several thousand years of intensive human harvesting. The conclusions presented here challenge the conventional wisdom regarding prehistoric landscape ecology in North America and have important implications for analyses that require information on long-term population histories, including those involving modern patterns in genetic diversity directed toward conservation related problems.